Chronic urticaria reveals JAK2V617F positive essential thrombocythemia - Albanesi, Marcello; Zurlo, Marco; Magistà, Stefania; Chaoul, Nada; Minenna, Elena; Satriano, Francesco; Bona, Danilo Di; Nettis, Eustachio; Caiaffa, Maria Filomena; Macchia, Luigi (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Urticaria is characterized by recurrent itchy wheals and/or angioedema and is usually classified as chronic urticaria (CU), if clinical symptoms persist for more than 6 weeks. In spontaneous CU, by definition, no specific triggers are associated with the appearance of signs and symptoms. One of the main underlying mechanisms responsible for urticaria is the activation of skin mast cells, which release histamine and other pro-inflammatory mediators involved in wheal formation and itch [1]. Aside from mast cells, other histamine-bearing cells exist, such as basophils, endothelial cells, gut cells, brain cells, smooth muscle cells and platelets. In particular, platelets contain a broad range of biological mediators: preformed mediators, such as histamine and serotonin, and newly formed mediators, such as platelet activating factor (PAF), leukotrienes and prostaglandins [2].